Competition for nitrogen between Fagus sylvatica and Acer pseudoplatanus seedlings depends on soil nitrogen availability - Li, Xiuyuan; Rennenberg, Heinz; Simon, Judy (Frontiers in Plant Science, 2015)
Competition for nitrogen (N), particularly in resource-limited habitats, might be avoided by different N acquisition strategies of plants. In our study, we investigated whether slow-growing European beech and fast-growing sycamore maple seedlings avoid competition for growth-limiting N by different N uptake patterns and the potential alteration by soil N availability in a microcosm experiment. We quantified growth and biomass indices, 15N uptake capacity and N pools in the fine roots. Overall, growth indices, N acquisition and N pools in the fine roots were influenced by species-specific competition depending on soil N availability. With interspecific competition, growth of sycamore maple reduced regardless of soil N supply, whereas beech only showed reduced growth when N was limited. Both species responded to interspecific competition by alteration of N pools in the fine roots; however, sycamore maple showed a stronger response compared to beech for almost all N pools in roots, except for structural N at low soil N availability. Beech generally preferred organic N acquisition while sycamore maple took up more inorganic N. Furthermore, with interspecific competition, beech had an enhanced organic N uptake capacity, while in sycamore maple inorganic N uptake capacity was impaired by the presence of beech. Although sycamore maple could tolerate the suboptimal conditions at the cost of reduced growth, our study indicates its reduced competitive ability for N compared to beech.